Calculation of the goffered multilayered composite cylindrical shells by using the finite element method - Toan, Pham Thi (Vietnam Journal of Mechanics, 1999)
In the present paper, the goffered multilayered composite cylindrical shells is directly calculated by finite element method. Numerical results on displacements, internal forces and moments are obtained for various kinds of external loads and different boundary conditions.